A dual source switched-capacitor converter with solar energy integration capability. (2017) - Abraham, Chikku; Jose, Babita Roslind; Mathew, Jimson
This paper presents a dual source variable output switched capacitor that can be operated in step down mode. The feature of the converter is that it can be selectively switched between two input sources one being a solar source. Since inductors are eliminated in the circuit topology the converter is light in weight and size. Also EMI issues are minimal due to the absence of inductors. The converter working in the no charge (NC) mode or fast switching limit (FSL) is used to develop the mathematical model. Using this model the equivalent resistance of the converter due to the influence of switch resistance and ESR of the capacitor can be found out. PSIM simulation of the converter gives satisfactory results and a laboratory prototype has been set up for experimental validation using the locally available components. The converter input is fixed at 12 V which can be from a battery source or solar source. The output variable voltage obtained is half, one-third, two-third and unity with respect to the input. The application of this converter can be in portable electronic devices or a processor for future which need three buck voltage levels typically in active, standby and sleep mode.